Formulation and Evaluation of Olibanum Gum Based Rabeprazole Buccal Tablets as Permeation Enhancing System - Rajput, Neha (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTBuccoadhesive tablet of Rabeprazole sodium was developed to prolong its release and improve bioavailability by avoidance of hepatic first pass metabolism. The bilayered buccoadhesive tablets were prepared by direct compression technology, using different mucoadhesive polymers such as carbopol-934 as primary, xanthum gum & olibanum gum as secondary polymer, sodium deoxycholate as permeation enhancer. The tablets were evaluated for Physical characterization, assay, swelling index, bioadhesion study, in-vitro residence time, microenvironment pH, in-vitro drug release and in vitro permeation. Bioadhesive strength tends to quite linear with increasing amount of each polymer. Percentage release of drug tented to very non-linear with polymer amount. The formulation (F13) with CP and OG containing 1:1 ratio including sodium deoxycholate was considered as an optimized formulation. The drug release of this formulation was found to be non-Fickian and approaching zero order kinetics. The optimized formulation was carried out for stability studies; the result indicated that no significant change with respect to adhesive strength, in vitro residence time, in vitro drug release and in vitro permeation study